Iron supplementation compliance among pregnant women in Bicol, Philippines - Lutsey, Pamela L.; Dawe, David; Villate, Ellen; Valencia, Shiela; Lopez, Ofelia (Cambridge University Press, 2008)
To quantify factors influencing iron supplementation compliance and haemoglobin (Hb) concentrations among pregnant women participating in an iron supplementation programme under routine field conditions.Cross-sectional interviews and Hb measurements.Albay and Sorsogon provinces, Bicol, Philippines.Three hundred and forty-six pregnant women receiving iron supplements via the Philippine iron supplementation programme.Women had a mean Hb concentration of 10.75 ± 1.43 g dl−1, and 56.4% were anaemic (Hb < 11.0 g dl−1). On average, the first prenatal visit occurred at nearly 4 months (3.80 ± 1.56). The ratio of visits to number of months pregnant was 0.51 ± 0.24. Self-reported consumption of pills received was 85% (0.85 ± 0.23), although pill counts suggested that consumption was 70% (0.70 ± 0.35). Using multiple regression, an earlier first prenatal visit and greater self-reported compliance were positively associated with Hb concentrations. Additionally, perceived health benefits from taking the supplements and higher health programme knowledge were positively associated with pill consumption, while experiencing side-effects and disliking the taste of the supplements were associated with lower pill consumption. A greater number of living children was negatively associated with the frequency of prenatal visits. The number of children was also directly negatively associated with Hb concentrations.Compliance was positively related to Hb concentrations. Several factors associated with greater compliance were identified, including marital status, number of children, health programme knowledge, side-effects, perceived health benefits, and dislike of taste. Some of these factors may serve as avenues for interventions to increase compliance, and ultimately Hb concentrations.